ASSOCIATION BETWEEN BRAIN VOLUMES AND PATTERNS OF COMMUNITY-DWELLING PHYSICAL ACTIVITY. (8th November 2019) - Wanigatunga, Amal A; An, Yang; Davatzikos, Christos; Urbanek, Jacek K; Spira, Adam P; Simonsick, Eleanor M; Resnick, Susan M; Schrack, Jennifer A
Abstract: With aging, brain structural integrity may influence patterns of physical activity (PA) performed in community-dwelling settings. In 281 cognitively-intact adults aged ≥65 years, linear regression models were fitted to examine whether MRI brain volumes (cc), assessed using an automated multi-atlas approach, were cross-sectionally associated with accelerometer-derived: 1) daily PA minutes and 2) activity fragmentation defined as the ratio of # of contiguous PA minutes over total PA minutes x 100. Higher white matter in the parietal and temporal lobes were associated with more daily active minutes (2.8 (SE=1.0) and 3.1 (0.9) min/day, respectively; p<0.005 for both) after adjusting for demographics, behavioral factors, medical conditions, and intracranial volume. Higher white matter in the temporal region was associated with lower fragmentation (-0.15 (0.05) %, p=0.004). Our results suggest sensorimotor-related brain morphometry is connected with both the amount and manner in which PA is performed throughout the day in well-functioning older adults.